Optimization of newcastle disease virus production in t-flask - Arifin, Mohd Azmir; Salim, Siti Hajar; Mel, Maizirwan; Abdul Karim, Mohamed Ismail; Syed Hassan, Sharifah (2011)
In this work, the propagation of Asplin F strain of Newcastle disease virus (NDV) in DF-1 cells was investigated. Experiments were carried out in T-flask to investigate the effects of serum concentration in the culture medium during virus replication phase and multiplicity of infection (MOI) on virus production. Virus infectivity titre of 6.62 x 107 TCID50/ml was achieved when serum concentration of 0.5% and MOI of 20 was used.